Integrating policy, technology, and knowledge: a roadmap to circular manufacturing adoption - Kiran Nair; Seema Bhardwaj; Ritika Chopra; Sreejith Balasubramanian; Mahima Mishra (International Journal of Sustainable Engineering)
Circular Manufacturing (CM) is a manufacturing process that employs strategies such as remanufacturing and closed-loop supply chains to improve sustainability (Delpla, Kenné, & Hof, 2022). This process employs circular economic principles. The adoption of CM has been impeded by a lack of financial support, inadequate consumer awareness, and insufficient government support. This review aims to facilitate a broader understanding of the adoption of government policies in implementing circular manufacturing strategies, which will help in advancing our knowledge about how nations compete to create and capture value. To provide a comprehensive and global perspective, the review included 524 studies from the Scopus Database, covering studies between 1990 and May 2024. The review contributes to (a) outlining three thematic clusters of shared scholarly interest, (b) the conceptual framework, and (c) highlighting several areas for future research. Ineffective management and sharing of information are significant challenges that impede organisational knowledge and decision-making administration. The transition to CM is facilitated by identifying essential data and technologies through an integrative review (bibliometric analysis and conceptual framework).